PELATIHAN KOMUNIKASI EFEKTIF PADA KARYAWAN RSU ANNA MEDIKA (Jurnal AbdiMas Nusa Mandiri, 2024)
The hospital is an organizer service health in a way plenary. Communication become a very important thing in the giving process of service health. Interaction between officers at home become a basic thing for everyone to do services provided to patient can done optimally. Communication effectively not only between officers with patients but also between officers at home sick. Communication effectively at home sick will minimize doubt in the patient regarding a series of treatment processes so that the patient will obey what is informed or recommended by the officer of health and so on no direct can increase the quality of home service. The purpose of the activity devotion public is to give importance to understanding officer health-related communication effective in giving service health good communication officer to patients between officer health at home sick. Activity training there are several suite activities among them offering material communication effective SBAR method and 7C formula, administration evaluation consisting of the pre-test and post-test, and roleplay for each case. Results of activities training enhanced understanding by participants related to communication effective besides That activity this is also a reminder return about material communication effective ever obtained moment lectures. There is an enhancement in the average pre-test score is 5.12 and the average post-test score is 9.06 on the SBAR method and there are increase in understanding of communication effective use 7C formula (pretest mean score of 5.25 and post-test mean score of 9.25).
Keywords: communication; effective; SBAR; 7C formula